2019
DOI: 10.1177/0963662519878988
|View full text |Cite
|
Sign up to set email alerts
|

Highly esteemed science: An analysis of attitudes towards and perceived attributes of science in letters to the editor in two Dutch newspapers

Abstract: Understanding attitudes towards science is crucial to safeguard the future of science, the application of its results and the inclusivity of decision-making processes related to science and technology. Most studies focus on attributes of social groups to explain attitudes towards science. In this study, we aim to move the discussion forward by focusing on perceived attributes of science itself by analysing over 300 letters to the editor in two Dutch national newspapers. The authors of these letters express a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…In detail, we used the search function of both platforms to identify especially opinionated user comments on relevant posts by strategically selected sources, i.e. tabloids known for their less‐educated (De Jong et al, 2020 ), vocal and discontented (Kemmers et al, 2015 ) reader base: Algemeen Dagblad and De Telegraaf . If any social media pages were then identified that seemed to be relevant based on the same criteria, they were added as sources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, we used the search function of both platforms to identify especially opinionated user comments on relevant posts by strategically selected sources, i.e. tabloids known for their less‐educated (De Jong et al, 2020 ), vocal and discontented (Kemmers et al, 2015 ) reader base: Algemeen Dagblad and De Telegraaf . If any social media pages were then identified that seemed to be relevant based on the same criteria, they were added as sources.…”
Section: Methodsmentioning
confidence: 99%
“…This is echoed in anecdotal evidence, comprising semistructured, inductive observations performed for this study of hundreds of social media reactions (Facebook comments and Tweets). These comments were in response to health promotion‐related news posts from media outlets commonly consumed by less‐educated individuals in the Netherlands (De Jong et al, 2020 ; Kemmers et al, 2015 ) and were translated here for matters of readability and anonymity. They reveal that some perceive such interventions as attempts to interfere with their freedom to choose, with one commenter stating: “Everyone should decide what to eat him‐or herself.…”
Section: A Novel Explanation For Less‐educated Individuals’ Limited N...mentioning
confidence: 99%
“…In such a condition, one's accurate attitude toward science will determine their level of belief in science (Wintterlin et al, 2022). In line with it, community ATS is crucial to preserve the sustainability of science and technology development (de Jong et al, 2020). According to the instructional aspect, ATS correlates with cognitive learning outcomes (Kristiani et al, 2016) and students' science achievements (Mao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%